Issues of measuring and accounting for social capital in digitalization - Serhii Fedorovych Lehenchuk; Dmytro Mykolaiovych Zakharov; Tetiana Petrivna Nazarenko (Економіка, управління та адміністрування)
The research paper provides a comprehensive analysis of the challenges in measuring and accounting for social capital in the context of digitalization. Social capital, encompassing social networks, trust, and social norms, plays a key role in creating added value and ensuring the sustainable development of both business and society. In terms of intangible nature of social capital, its assessment and representation in accounting practices remain complex, especially in the context of rapid transformations driven by digital technologies. The article examines the impact of digitalization on social capital, highlighting both positive aspects, such as increased accessibility to social networks and new opportunities for collective action, and risks, including the creation of weak ties and information polarization. Recommendations from the International Integrated Reporting Council (IIRC) and A4S guidelines are explored, emphasizing the importance of considering social capital as an integral component of performance measurement for enterprises. A proposed three-step approach to social capital assessment is presented, encompassing corporate, project, and product levels, ensuring a comprehensive evaluation of its impact on the value chain. The study also examines the influence of digital platforms on trust-building processes, approaches to measuring community engagement, and opportunities for supporting broad social networks. The research paper underscores that the integration of social capital into organizational processes contributes to a deeper understanding of value creation sources, enhances corporate reputation, strengthens relationships with stakeholders, and opens new market opportunities. Alongside the benefits of digitalization, social capital also faces new challenges, particularly the need to incorporate both qualitative and quantitative metrics to reflect its significance in reporting. The research emphasizes the importance of developing adaptive methods for assessing social capital, considering the specificities of the digital environment and the evolving nature of social interactions.